A Real-Business-Cycle Model with Financial Liberalization: Lessons for Bulgaria (1999-2020) - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance; Vol 8 No 1 (2022): JMEF, Volume VIII, issue 1(14), Summer 2022DO - 10.14505/jmef.v8.1(14).01, 2022)
Financial openness is introduced into a real-business-cycle setup aug- mented with a detailed government sector. The model is calibrated to Bulgarian data for the period following the introduction of the currency board arrangement (1999- 2020). The quantitative importance of financial openness is investigated for the stabi- lization of cyclical fluctuations in Bulgaria. The computational experiment performed in this paper reveals that greater financial openness increases the impact of technology shocks on output, investment, consumption, labor hours, and net exports. This am- plification effect is due to the following mechanism: openness provides a cheap access to foreign funds. Unfortunately, the new results come at odds with a major empirical observation, i.e. that consumption and net exports strongly pro-cyclical; the model, however, produces a countercyclical consumption, as well as net exports. Thus, such a setup is not yet ready to be used for policy analysis.